2020
DOI: 10.3389/fpubh.2020.575091
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Change Towards Reduced Intensity Physical Activity Is Disproportionately Prevalent Among Adults With Serious Health Issues or Self-Perception of High Risk During the UK COVID-19 Lockdown

Abstract: Objectives: We assessed whether lockdown had a disproportionate impact on physical activity behavior in groups who were, or who perceived themselves to be, at heightened risk from COVID-19. Methods: Physical activity intensity (none, mild, moderate, or vigorous) before and during the UK COVID-19 lockdown was self-reported by 9,190 adults between 2020-04-06 and 2020-04-22. Physician-diagnosed health conditions and topic composition of open-ended text on participants' coping strategies were tested for associatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
160
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(178 citation statements)
references
References 20 publications
15
160
2
1
Order By: Relevance
“…Meanwhile, the% of United Kingdom citizens of both sexes (20 years old) reported equal levels of physical activity intensity during the lockdown period, compared to the pre-pandemic period. These findings were more obvious for males, while other factors, such as living alone or the existence of a garden in the house, also influenced the results (Rogers et al, 2020). In adult Canadians, 22.4% of the participants that were self-reported as "active" became less active, while 40.3% became more active.…”
Section: Physical Inactivity In the Pandemicmentioning
confidence: 87%
“…Meanwhile, the% of United Kingdom citizens of both sexes (20 years old) reported equal levels of physical activity intensity during the lockdown period, compared to the pre-pandemic period. These findings were more obvious for males, while other factors, such as living alone or the existence of a garden in the house, also influenced the results (Rogers et al, 2020). In adult Canadians, 22.4% of the participants that were self-reported as "active" became less active, while 40.3% became more active.…”
Section: Physical Inactivity In the Pandemicmentioning
confidence: 87%
“…This is confirmed by the finding that 43% of our respondents reported doing less overall PA at the beginning of June 2020 in comparison to the weeks prior to the lockdown in mid-March 2020. Other studies reported similar shifts in PA among UK adults during April 2020 (Rogers et al, 2020;Sport England, 2020) and decreases in the proportion meeting guidelines in the United States (Meyer et al, 2020). The second objective was to investigate the usefulness of the COM-B model (Michie et al, 2011) in predicting shifts in PA modalities during the lockdown.…”
Section: Discussionmentioning
confidence: 97%
“…All reported some form of decrease in PA from before to during the shutdown, whereas three of the studies also reported no change (Rogers et al, 2020 ; Smith et al, 2020 ) or an increase in PA (Cheval et al, 2020 ) for some specific groups. This may be due to poor measures of PA and small sample sizes as two of the studies did not report a specific PA measurement tool used (Rogers et al, 2020 ; Smith et al, 2020 ), and one of the studies only included 267 participants (Cheval et al, 2020 ). Seven of the studies were cross-sectional, using retrospective and self-reported online surveys to measure PA, whereas one was a longitudinal study that used device-based PA monitoring (Ong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies from different European, Asian, and American countries have—to some degree—investigated the impact of the COVID-19 shutdown on PA behavior (Cheval et al, 2020 ; López-Bueno et al, 2020 ; Maugeri et al, 2020 ; Ong et al, 2020 ; Rhodes et al, 2020 ; Rogers et al, 2020 ; Smith et al, 2020 ; Yamada et al, 2020 ). All reported some form of decrease in PA from before to during the shutdown, whereas three of the studies also reported no change (Rogers et al, 2020 ; Smith et al, 2020 ) or an increase in PA (Cheval et al, 2020 ) for some specific groups. This may be due to poor measures of PA and small sample sizes as two of the studies did not report a specific PA measurement tool used (Rogers et al, 2020 ; Smith et al, 2020 ), and one of the studies only included 267 participants (Cheval et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%